2017
DOI: 10.1590/1678-4685-gmb-2016-0087
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between plant hormones and heavy metals responses

Abstract: Heavy metals are natural non-biodegradable constituents of the Earth's crust that accumulate and persist indefinitely in the ecosystem as a result of human activities. Since the industrial revolution, the concentration of cadmium, arsenic, lead, mercury and zinc, amongst others, have increasingly contaminated soil and water resources, leading to significant yield losses in plants. These issues have become an important concern of scientific interest. Understanding the molecular and physiological responses of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
166
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(175 citation statements)
references
References 137 publications
5
166
0
4
Order By: Relevance
“…We would like to stress that an increase in the IAA and flavonol content have been proposed as the key factors in hormesis here for the first time. In general, the literature on metals and hormesis is dominated by studies on the role of oxidative stress and phytohormones such as abscisic acid, ethylene or jasmonates, with little information on the role of IAA and flavonols [3,4,6,41,54]. The results presented here also suggest that an increase in the photosynthesis and transpiration rates are not necessary for stimulating hormetic growth.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…We would like to stress that an increase in the IAA and flavonol content have been proposed as the key factors in hormesis here for the first time. In general, the literature on metals and hormesis is dominated by studies on the role of oxidative stress and phytohormones such as abscisic acid, ethylene or jasmonates, with little information on the role of IAA and flavonols [3,4,6,41,54]. The results presented here also suggest that an increase in the photosynthesis and transpiration rates are not necessary for stimulating hormetic growth.…”
Section: Discussionmentioning
confidence: 67%
“…Phytohormones such as auxins have been found to play an important role in plant tolerance and the alleviation of the stress that is induced by HMs [54]. It has been suggested that the cellular level of auxins increases under a low level of abiotic stress, which stimulates vegetative growth, thus leading to the hormetic effect [3,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABA signaling has been considered as an important factor in Cd-signal transduction. A rapidly increase on ABA's level under stressful conditions triggers response mechanisms via several ABA-responsive genes, ultimately leading to physiological changes such as the rapid closing of stomata (Asgher et al 2015;Bücker-Neto et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…В умовах стресу концентрація гормону стрімко зростає, що дає змогу рослині адаптуватися та вижити [18]. Накопичення ендогенної АБК і подальше гальмування росту розглядають як адаптивну реакцію, спрямовану на збереження життєздатності рослини в несприятливих умовах і подальше відновлення після припинення стресового впливу [7]. АБК відіграє головну роль у регулюванні вмісту води контролем продихової провідності, а індуковане гормоном закриття продихів відбувається впродовж кількох секунд або хвилин від початку дії стресора [13].…”
unclassified